Pain and pain management in haemophilia. Issue 8 (December 2016) - Auerswald, Günter; Dolan, Gerry; Duffy, Anne; Hermans, Cedric; Jiménez-Yuste, Victor; Ljung, Rolf; Morfini, Massimo; Lambert, Thierry; Šalek, Silva Zupančić
Abstract : Joint pain is common in haemophilia and may be acute or chronic. Effective pain management in haemophilia is essential to reduce the burden that pain imposes on patients. However, the choice of appropriate pain-relieving measures is challenging, as there is a complex interplay of factors affecting pain perception. This can manifest as differences in patients' experiences and response to pain, which require an individualized approach to pain management. Prophylaxis with factor replacement reduces the likelihood of bleeds and bleed-related pain, whereas on-demand therapy ensures rapid bleed resolution and pain relief. Although use of replacement or bypassing therapy is often the first intervention for pain, additional pain relief strategies may be required. There is an array of analgesic options, but consideration should be paid to the adverse effects of each class. Nevertheless, a combination of medications that act at different points in the pain pathway may be beneficial. Nonpharmacological measures may also help patients and include active coping strategies; rest, ice, compression, and elevation; complementary therapies; and physiotherapy. Joint aspiration may also reduce acute joint pain, and joint steroid injections may alleviate chronic pain. In the longer term, increasing use of prophylaxis or performing surgery may be necessary to reduce the burden of pain caused by the degenerative effects of repeated bleeds. Whichever treatment option is chosen, it is important to monitor pain and adjust patient management accordingly. Beyond specific pain management approaches, ongoing collaboration between multidisciplinary teams, which should include physiotherapists and pain specialists, may improve outcomes for patients.